Personal attitude and entrepreneurial intention: Examining the mediating effect of self-efficacy among non-business students - Abu Bakar, Hatinah; Abdull Rahim, Mohd Faisal; Sakarji, Siti Rosnita; Wan Husin, Wan Zakiyatussariroh (Journal of Islamic, Social, Economics and Development, 2026)
Entrepreneurship is increasingly recognized as a catalyst for sustainable economic growth, innovation, and social development. In Malaysia, universities play a vital role in cultivating entrepreneurial capabilities; however, many graduates lack the confidence to translate academic knowledge into venture creation. This study examines the influence of personal attitude on entrepreneurial intention and investigates the mediating role of self-efficacy among non-business students at Universiti Teknologi MARA, Kelantan Branch. Adopting a quantitative research design, data were collected from 184 students across various faculties—including Accountancy, Computer & Mathematical Sciences, Information Management, and Arts & Design. Participants were selected via purposive sampling based on a strict exclusionary criterion. The data were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that personal attitude has a significant positive effect on entrepreneurial intention and significantly influences self-efficacy. Self-efficacy also mediates the relationship between personal attitude and entrepreneurial intention, indicating that students with positive attitudes are more likely to develop entrepreneurial intentions when they possess strong confidence in their entrepreneurial abilities. The model explains a substantial proportion of variance in entrepreneurial intention, highlighting the importance of personal attitude factors in shaping entrepreneurial mindset.